2014
DOI: 10.1016/j.chom.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Neutralizing Influenza Hemagglutinin Stem-Specific Antibody CR8020 Targets Residues that Are Prone to Escape due to Host Selection Pressure

Abstract: SUMMARY Broadly neutralizing antibodies (bNAb) that target a conserved region of a viral antigen hold significant therapeutic promise. CR8020 is a bNAb that targets the stem region of influenza A virus (IAV) hemagglutinin (HA). CR8020 is currently being evaluated for prophylactic use against group 2 IAVs in phase II studies. Structural and computational analyses reported here indicate that CR8020 targets HA residues that are prone to antigenic drift and host selection pressure. Critically, CR8020 escape mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 33 publications
2
43
0
1
Order By: Relevance
“…Unfortunately, CR8020 has been less effective against the recent H7N9 virus 27 . In this study, we generated a combinatorial library with blood from patients recovering from H7N9 infection and screened this library for neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, CR8020 has been less effective against the recent H7N9 virus 27 . In this study, we generated a combinatorial library with blood from patients recovering from H7N9 infection and screened this library for neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…One mutant completely abolished binding of antibody 39.29 to the HA stem, whereas the other two mutants escape by increasing fusion efficiency [118]. Other examples include escape mutants against stem-binding bnAbs C179 [103], CR8020 [107, 119], CR6261 [108], and CR8043 [109]. Although some escape mutants against stem-binding bnAbs have been shown to reduce viral replication fitness [106, 118], compensatory mutations may exist.…”
Section: Functionally Conserved Region 2: Membrane Fusionmentioning
confidence: 99%
“…It has been demonstrated that those conserved regions in structural proteins have an important role in viral fitness and might be targets of broadly neutralising antibodies in viruses such as HIV and Influenza A virus. For instance, although the majority of the protective immune response against influenza virus is provided by antibodies against the head of haemagglutinin (HA), new classes of multi-neutralising antibodies have been isolated that target the highly conserved HA stalk region121314151617. Antibodies with similar properties have also been found that target functionally conserved regions of HIV glycoprotein 1201819202122.…”
mentioning
confidence: 99%